Analysis of external auditor reports on performance auditing of federal statutory bodies / Associate Professor Dr. Asmah Abdul Aziz, Mohd Faidzal Abu and Amal Hayati Aziz - Abdul Aziz, Associate Professor Dr. Asmah; Abu, Mohd Faidzal; Aziz, Amal Hayati (Research Management Institute (RMI), 2012)
The statutory body is required to comply with the government procedures such as the remuneration system, employment scheme and the operational policies. The audited annual accounts of statutory bodies and audit certificates issued by the Auditor General might be useful to keep an eye on the accountability functions hold by statutory bodies with the aim to reduce information costs and the problem between citizens and the government. This study examines the Auditor General‟s Report of selected statutory bodies in Malaysia. The main aspect emphasized in this study is the types of audit incidents exist in the report. Eleven of the selected statutory bodies were analysed for five years from year 2003 to 2007. It is essential to investigate the audit incidents presented by the auditors in the audit certificates. It will assist the users of financial report and government entities to focus on areas highlighted by auditors for further improvement, to avoid repeated flaws, and to obtain clean audit report in the future. There are numerous types of comments indicated by the auditors. In the areas of financial reporting of statutory bodies, the most frequent comments as being indicated by the auditors in their reports are incomplete records; and non-compliance with other laws. Moreover, in the areas of non-financial reporting of statutory bodies, the most frequent audit incidents are weakness in service provided; inappropriate security procedures; and inefficient administration and operation. As for the conclusion, the occurrence of auditors‟ comments on financial reports should motivate the responsible members of respective statutory bodies to obtain a clean report in the following years and in the future. The regulator and government agencies‟ teams have to overcome any flaws found by the auditor in both financial and non-financial reporting and to avoid such weaknesses to be repeated in future.